Integrated process for extraction and formulation in emulsions of active molecules from fresh passion fruits (Passiflora edulis Sims). (December 2019) - Delvar, Alice; de Caro, Pascale; Candy, Laure; Caro, Yanis; Cheong Sing, Alain Shum; Raynaud, Christine
Abstract: Intensified green processes were investigated to extract several classes of active molecules from fresh purple passion fruits, and to prepare emulsions directly by extrusion for the fruit comprehensive utilization. A thermo-mechanical treatment was carried out through a discontinuous process from the edible part and through a continuous process by twin-screw extrusion using the whole fruit. Only mechanical energy was applied to the materials to generate a liquid fraction (filtrate) and a solid residue. Lipid contents of the obtained filtrates ranged from 0.5 to 2.6 g/100 g close to the extractible lipophilic part. Polyphenols extraction was improved when using the whole fruit and with the addition of water in extrusion. In-situ emulsions with droplets sizes between 2 and 8 μm were obtained. Emulsions obtained after extrusion showed an enhanced stability. This way represents a green alternative method to solvent extractions applied to the different parts of the fruit, and leads to bio-based emulsions enriched in vegetable oil, natural antioxidants and emulsifiers, such as phospholipids, proteins, polysaccharides, pectins and polyphenols. Highlights: Filtrates from passion fruit are obtained by mechanical activation based processes. Simultaneous extraction of active molecules leads to in situ o/w emulsions. The stabilities of emulsion are correlated to rheology and light scattering analyses. The discontinuous process leads to emulsions rich in lipids and proteins. Extrusion of the whole fruit results in stable emulsions.